Pengaruh Perbandingan Bahan Pengisi (alumina-magnesia-silika) Terhadap Karakteristik dan Kekerasan Nanokomposit Berbasis Geopolimer untuk Aplikasi Bracket Ortodontik Cekat - Kiky Viviani; Angela Evelyna; Bambang Sunendar Purwasasmita (Jurnal Material Kedokteran Gigi, 2018)
Ceramic bracket has advantage that good aesthetic and good hardness, however it has weaknesses which are high cost and brittle so that, it needed others alternative substances such as composite. Nanocomposite has grown in many regions, one of them is in dentistry. Nanocomposite frequently used because of synthesis relative simple and it can increase characteristics substance. This study was alumina, magnesia, silica synthesized with sol-gel technique for filler of nanocomposite based geopolymer. The purposes of this study are to obtain initial characteristics and hardness of nanocomposite aluminamagnesia-silica. Specimens of this study were nanocomposite with ratio filler alumina-magnesia-silica 48:40:12 (group I) and 65:30:5 (group II). XRD used to determine the crystalline phase and composition filler powder alumina-magnesia-silica, whereas SEM and Vickers hardness test used to determine the morphology microstructure and hardness nanocomposite surface. XRD test represent phase magnesia alumina spinel formed in both groups, with crystalline size are 30-39 nm. SEM test of group I represent particle dispersion more prevalent, whereas SEM test of group II represent agglomeration particle and porous. The average of group I was 60,16 VHN, while the average of group II was 6,98 VHN. Visualization nanocomposite of group I represent transparent color and group II represent white opaque color. Conclusion of this study is nanocomposite with ratio of filler alumina- magnesia-silica 48:40:12 (group I) has particle dispersion more prevalent and hardness higher than nanocomposite with ratio of filler alumina-magnesia-silica 65:30:5 (group II), but the application as a bracket fixed orthodontic further study is needed.